Gold Currency Model in Aceh - Bedjo Santoso Kadri (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. Complementary currency has been a trending issue. This is because the complementary currency can reduce people’s dependency on the government in serving the currency as a medium of exchange. However, many studies neglected the role of idle gold. Aceh is one province of Indonesia that reserves the right of special autonomy to implement Sharia. Aceh, being renowned for its fertility in the cultivation of some agricultural products such as coffee, tobacco, and palm oil, has become a strategic trade center. Aceh is also equally rich in gold mines, with the approximate result of five tons a year. This research attempts to design a model of complementary currency based on physical gold in Aceh. This study uses unstructured interviews with scholars, leaders, business people, and the government. The result reveals that stakeholders agree with the gold complementary currency, support and willing to recommend it. Besides, this model is believed to be beneficial. However, the most challenging factor is the support from the government which is essential to develop this gold currency model.Keywords: Complementary Currency, Aceh Economy, Gold-Based Money, Islamic Currency. Abstrak. Mata uang komplementer (complementary currency) menjadi isu yang masih terus menjadi pembahasan. Hal ini karena mata uang komplementer dapat mengurangi ketergantungan terhadap pemerintah dalam melayani kebutuhan mata uang sebagai media pertukaran. Mata uang komplementer, termasuk yang berbasis emas, dapat meningkatkan ketahanan masyarakat terhadap krisis moneter. Namun demikian, kajian tentang hal ini masih jarang, terutama tentang peranan emas yang menganggur (idle gold). Aceh merupakan satu provinsi di Indonesia yang memiliki hak otonomi khusus untuk menerapkan syariat Islam. Penelitian ini mencoba merekomendasikan model mata uang komplementer berdasarkan emas, untuk diimplementasikan di Aceh. Penelitian dilakukan dengan wawancara tidak terstruktur dengan stakeholders dari ulama, pemimpin masyarakat, pelaku bisnis, dan pemerintah. Hasilnya menunjukkan bahwa stakeholders setuju, mendukung, dan merekomendasikan penggunaan mata uang komplementer di Aceh. Selain itu, model ini dipercaya dapat bermanfaat bagi perekonomian, kehidupan sosial, dan penerapan nilai Islam serta persaidaraan. Namun demikian, tantangan yang paling utama adalah dukungan pemerintah dan keterlibatannya dalam pengembangan dan implementasi model ini.Kata kunci: Complementary Currency, Aceh Economy, Gold-Based Money, Islamic Currency